Conversations with Those Who Ask About War (transcript Verlag, 2026)
How can good practices be developed for collecting, preserving, and publishing eyewitness accounts of a war that is still ongoing? The contributions offer insights into specifics of interviewing witnesses of the first months of Russia’s full-scale invasion of Ukraine. Each chapter introduces researchers and practitioners who began documenting the war while living through it, driven by a desire for justice, preservation of memory, and community building. As a dialogic and multifaceted volume, it welcomes collaborative thinking and serves as a methodological guide and a space for frankness and sensitivity, capturing the academic community’s response to the challenges posed by extraordinary circumstances and existential threats.